HUBUNGAN KEBIASAAN MAKAN DENGAN STATUS GIZI PADA REMAJA SMP YLPI PEKANBARU - Dian Hafiza (Jurnal Medika Hutama, 2020)
Puberty needs more nutrients due to the physical growth and the development occurred during the transition from childhood to adolescence. The change of lifestyle and teenager’s eating habits influence nutritional intake and needs. Eating habits in teenagers is related to the food consumption of food types, food amounts, food frequency, food distribution and the way of choosing food. The unhealthy eating habits are formed due to buying snacks outside the house regularly which will influence teenager’s nutrients status. The aim of this study is to find out the relation of eating habit to the nutritional status in teenager of JHS. The study used correlative-descriptive design with cross-sectional approach. The total samples in this study were 76 respondents. The sample collection technique used Quota Sampling. The study instrument used Adolescent Food Habits Checklist (AFHC) questionnaire, body weight measurement used bathroom schale and body height used microtoise. The analysis used was univariate and bivariate analysis, by using non-parametric statistic with alternative test which was kolmogorov smirnov. The result of the study is the P value 1 > a (0.05). It can be concluded that there is no correlation between eating habits and the nutritional statues of teenager in YLPI Junior High School Pekanbaru. It is suggested for the teenager to extend their knowledge of healthy eating habits.